The Correlation Between Migraine and Patent Foramen Ovale - Liu, Kaiming; Wang, Brian Z.; Hao, Yishu; Song, Shuijiang; Pan, Mengxiong (Frontiers in Neurology, 2020)
Background: Migraine is a widespread neurological disorder. Patent foramen ovale (PFO) is a construction in fetal circulation but forms a flap remnant in about 20-30% of adults. Migraine has been associated with PFO for the relationship between the incidence rate of two. However, percutaneous closure of PFO in patients with migraine headaches is still controversial. Methods: An electronic literature was screened to review studies about the relationship between PFO and migraine and the effects of treatments on migraine attacks. Results: After a brief summary of potential pathophysiological mechanisms, this systemic review firstly elaborates on migraine type, migraine frequency, clinical symptoms of migraine with PFO and the state, the size, the anatomical structures of PFO with migraine, respectively. Finally, it lays out the effects of PFO closure on migraine attacks. Conclusion: Migraine and PFO may support a dose-response relationship, which addresses the proper assessment of patients for PFO closure interventions, but the relevant risk of serious adverse events should be considered.